Effect of Standard vs Intensive Blood Pressure Control on the Risk of Recurrent Stroke - Priscilla, Priscilla; Verawati, Verawati (The International Journal of Medical Science and Health Research, 2024)
Background: The literature surrounding blood pressure management in patients with a history of stroke has evolved significantly over the past few years, reflecting an increasing understanding of the complexities involved in optimizing treatment strategies for secondary stroke prevention. Literature Review: The literature reviewed illustrates the intricate relationship between blood pressure management and recurrent stroke risk, emphasizing the need for individualized treatment strategies. (Wang et al., 2016) provide a foundational overview of the effectiveness of various antihypertensive medications, highlighting angiotensin-converting enzyme inhibitors (ACEIs) and diuretics as key players in secondary stroke prevention. Conclusion: In conclusion, the literature presents a complex landscape of blood pressure management strategies for stroke patients, highlighting the importance of individualized approaches based on patient characteristics and specific clinical contexts. The evidence suggests that while intensive blood pressure control may offer certain protective benefits, it must be balanced with potential risks and tailored to the unique needs of each patient. Continued research is essential to refine these strategies and optimize outcomes for individuals at risk of recurrent strokes.